ANALISIS EDUITAINMENT DAN BRAIN BASED LEARNING PERSPEKTIF PSIKOLOGI PEMBELAJARAN PAI DAN AGAMA. (Program Studi Pendidikan Agama Islam, 2019)
Development of learning today sue to educators improve quality so that achieved expected learning purpose. a learning model which is seldom explored as creative and innovation teacher, specially Islamic study material is demanding rote such as the Qur’an, Hadith, Reading of short prayers, and short letters in teh Qur’an. Theory of edutainment and brain based learning is an exciting innovation learning model.understanding learning model can be an alternative for general teacher or Islamic education teacher to learn implementation it in a teaching and learning process. The research purposes analyze two theories in terms of the similarities and defferences in psychology of learning PAI (Islamic education) and psychology of religion. Researchers reviewing the literature from books, article and journals, analysis this study using a comparative analysis tested both using rational comparisons.